Actions of military veterinary medicine in a food defense context: a study under the perspective of the Brazilian Armed Forces based on American Armed Forces guidelines - FUSCO, Maria Alice; ABREU, Vitor Luiz Farias de (Food Science and Technology, 2023)
The perception that food supplies and any stage of manufacturing process chains can become vehicles for the intentional spread of biological, chemical, physical, and radiological contaminants took form after the September 11, 2001, attacks in the United States. Food defense thus emerged as a new area within the food safety field. Under this perspective, risks to food and food production chains originate from intentional and ideologically engineered acts that aim to harm public health on a wide scale. In times of international conflicts that aim to destabilize a nation’s morale, the armed forces may become a target for attacks, leading to operability losses and momentary or permanent troop losses due to foodborne illnesses or deaths caused by the massive contamination of food consumed by the military. In this regard, veterinarians enrolled in the armed forces can focus on defense measures against deliberate food supply contamination, as they are trained in food technology, inspection, and surveillance. This review summarizes the role of veterinarians in the food defense field in the United States Armed Forces and the current situation of these professionals in the Brazilian Armed Forces.